基于改进贸易引力模型的中国植物油料 进口流量及潜力分析Analysis of import flow and potential of China′s plant oilseed based on improved trade gravity model - 曹冲1,2，袁国军1,2，宋锋华3CAO Chong1,2, YUAN Guojun1,2, SONG Fenghua3 (Zhongguo youzhi)
旨在为保障国内油料安全提供参考依据,基于中国植物油料进口实际情况，构建改进的贸易引力模型，以2013—2022年中国植物油料进口贸易的26个国家为研究对象，实证考察中国植物油料进口流量的影响因素及潜力。结果表明：经济规模、地理距离、相似需求、边界相邻对中国植物油料进口起到促进作用，而人口规模、要素禀赋、开放程度、汇率水平、区域组织则对中国植物油料进口产生一定的阻碍作用；中国从巴西进口的植物油料属于“过度进口”，从蒙古国、美国、俄罗斯、巴基斯坦等22个国家进口的植物油料属于“进口饱和”，而从墨西哥、乌克兰、布基纳法索进口的植物油料属于“进口不足”。因此，需要提高国内植物油料生产效率和能力、鼓励国内企业积极参与植物油料进口市场、重视中国与植物油料贸易伙伴国的国别异质性、努力推动新兴市场战略等则有利于实现优势互补，进而保障国内植物油料安全。To provide a reference basis for ensuring the safety of domestic plant oilseed, an improved trade gravity model was constructed based on the actual situation of China′s plant oilseed import, and 26 countries of China′s plant oilseed import trade from 2013 to 2022 were used to investigate the influence factors and potential of China′s plant oilseed import flow. The results showed that economic scale, geographical distance, similar demand and adjacent borders played a promoting role in China′s plant oilseed import, while population size, factor endowment, openness degree, exchange rate level and regional organization had some hindering effect. Plant oilseed imported from Brazil was "excessive import", plant oilseed imported from 22 countries, including Mongolia, the United States, Russia and Pakistan, was "import saturation", while plant oilseed imported from Mexico, Ukraine and Burkina Faso was "insufficient import". Therefore, it is necessary to improve the efficiency and capacity of plant oilseed production of China, encourage domestic enterprises to actively participate in the plant oilseed import market, attach importance to the national heterogeneity between China and plant oilseed trading partners, and promote the promotion of emerging market strategy, which are conducive to realize complementary advantages and ensure the safety of domestic plant oilseed.